Determinación de tocoferoles, tocotrienoles mediante Cromatografía de Gases acoplado a Espectrometría de Masas y medición de la capacidad antioxidante usando el método de decoloración del catión radical ABTS+, empleando un espectrofotómetro UV-visible en cuatro especies de Arecaceae de la provincia de Loja y El Oro. - Cuenca Quezada, Karina del Cisne (2014)
Actually the consumption of vitamins is has increased because their antioxidant properties. These are mainly obtained from plant sources; including vitamin E as one of the most important to help prevent cancer and cardiovascular disease. Thus the importance of this research and the fact of there aren’t studies of these species in the Arecaceae. The fruits of 4 different species were collected in the provinces of Loja and El Oro, of which vegetable oil was extracted with the Soxhlet method. In a database Botany and Ethnobotany information of each of the species studied was detailed, certain physical properties such as refractive index, density, color and appearance was determined and proceeded to establish the method to inject the samples in the GCMS, for inject the samples in GCMS is necessary to purify to avoid equipment damage these were saponified and derivatized. It was possible to identify the presence of α-tocopherol in species Aiphanes grandis and Phoenix canariensis and α-tocotrienol in Syagrus romanzoffiana. The antioxidant activity was determined using the ABTS method, where it is noted that the species Syagrus romanoffiana possesses the greatest antioxidant activity and Phoenix canariensis lower.